Pleiotropic Effects of GLP-1 and Analogs on Cell Signaling, Metabolism, and Function - Rowlands, Jordan; Heng, Julian; Newsholme, Philip; Carlessi, Rodrigo (Frontiers in Endocrinology, 2018)
The incretin hormone Glucagon-Like Peptide-1 (GLP-1) is best known for its ‘incretin effect’ in restoring glucose homeostasis in diabetics, however, it is now apparent that it has a broader range of physiological effects in the body. Both in vitro and in vivo studies have demonstrated that GLP-1 mimetics alleviate endoplasmic reticulum stress, regulate autophagy, promote metabolic reprogramming, stimulate anti-inflammatory signaling, alter gene expression and influence neuroprotective pathways. A substantial body of evidence has accumulated with respect to how GLP-1 and its analogues act to restore and maintain normal cellular functions. These findings have prompted several clinical trials which have reported GLP-1 analogues improve cardiac function, restore lung function and reduce mortality in patients with obstructive lung disease, influence blood pressure and lipid storage, and even prevent synaptic loss and neurodegeneration. Mechanistically, GLP-1 elicits its effects via acute elevation in cAMP levels, and subsequent protein kinase(s) activation, pathways well defined in pancreatic β-cells which stimulate insulin secretion in conjunction with elevated Ca2+ and ATP. More recently, new studies have shed light on additional downstream pathways stimulated by chronic GLP-1 exposure, findings which have direct relevance to our understanding of the potential therapeutic effects of longer lasting analogues recently developed for clinical use. In this review, we provide a comprehensive description of the diverse roles for GLP-1 across multiple tissues, describe downstream pathways stimulated by acute and chronic exposure, and discuss novel pleiotropic applications of GLP-1 mimetics in the treatment of human disease.